Robotic-assisted versus laparoscopic bowel anastomoses: randomized crossover in vivo experimental study - Haney, Caelán Max; Kowalewski, Karl-Friedrich; Schmidt, Mona Wanda; Lang, Franziska; Bintintan, Vasile; Fan, Carolyn; Wehrtmann, Fabian; Studier-Fischer, Alexander; Felińska, Eleni Amelia; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2023)
Initial learning curves are potentially shorter in robotic-assisted surgery (RAS) than in conventional laparoscopic surgery (LS). There is little evidence to support this claim. Furthermore, there is limited evidence how skills from LS transfer to RAS.